2008
DOI: 10.6017/ital.v31i1.1855
|View full text |Cite
|
Sign up to set email alerts
|

Usability Test Results for a Discovery Tool in an Academic Library

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 18 publications
1
53
0
1
Order By: Relevance
“…It is noteworthy that because discovery tools are relatively recent, most of the published literature compares or evaluates products (Rowe, 2010;Yang & Wagner, 2010;Luther & Kelly, 2011;Gallaway & Hines, 2012;Hoeppner, 2012;Vaughan, 2012;Asher et al 2013) or describes implementation or usability studies at individual institutions (Gross and Sheriden, 2011;Howard and Wiebrands, 2011;Williams and Foster, 2011;Comeaux, 2012;Fagan et al 2012;Kaufmann et al 2012;Kornblau et al 2012;Fyn et al 2013). Several specifically discuss librarians' reaction to discovery tools (Buck & Mellinger, 2011;Howard & Wiebrands, 2011;Boyer & Besaw, 2012) and how students use them (Meadow & Meadow, 2012;Mussell & Croft, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is noteworthy that because discovery tools are relatively recent, most of the published literature compares or evaluates products (Rowe, 2010;Yang & Wagner, 2010;Luther & Kelly, 2011;Gallaway & Hines, 2012;Hoeppner, 2012;Vaughan, 2012;Asher et al 2013) or describes implementation or usability studies at individual institutions (Gross and Sheriden, 2011;Howard and Wiebrands, 2011;Williams and Foster, 2011;Comeaux, 2012;Fagan et al 2012;Kaufmann et al 2012;Kornblau et al 2012;Fyn et al 2013). Several specifically discuss librarians' reaction to discovery tools (Buck & Mellinger, 2011;Howard & Wiebrands, 2011;Boyer & Besaw, 2012) and how students use them (Meadow & Meadow, 2012;Mussell & Croft, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They conclude, the "literature illustrates a current need for more usability studies related to discovery tools." 4 The most relevant literature to this study are case studies documenting a library's experience with implementing a discovery services and task based usability studies of discovery services. Thomas and Buck 5 sought to determine with a task based usability study whether users were as successful performing common catalog-related tasks in WorldCat Local (WCL) as they are in the library's current catalog, Innovative Interfaces' WebPAC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While most tasks were accomplished successfully, the study confirmed previous warnings that users do not understand the complexities of search and identified several interface issues: (1) users desire single search, but willingly use multiple options for search, (2) lack of visibility for the option to sort search results, and (3) the difficulty in finding journal articles. [3] Yang and Wagner offer one case where the aim was to evaluate discovery layers against a check--list of 12 features that would define a true 'next generation catalogue':…”
Section: Related Work Discovery Layersmentioning
confidence: 99%
“…A comparison to usability study findings, as presented by Fagan et al, is offered as a way of conclusion. [3] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation